Revitalisasi Lembaga Adat sebagai Instrumen Pemberdayaan Masyarakat Aceh Studi Implementasi Pasal 98-99 UU Pemerintahan Aceh - Qodir, Ibnu; Buchari, Muhammad Al Akhyar (IAIN Takengon, 2025)
This research examines the implementation of Acehnese traditional institutions revitalization as an instrument of community empowerment based on the legal framework of Law No. 11/2006 on Aceh Governance. Employing a literature review approach with descriptive-qualitative methods, this study analyzes the normative foundation, implementation practices, and effectiveness of traditional institutions in performing community participation functions and social problem resolution. Primary data sources include Law No. 11/2006 and Qanun Aceh No. 10/2008, while secondary data encompasses journal articles, academic research, and literature related to traditional institution empowerment. Research findings indicate that the legal framework provides strong formal legitimacy for 13 types of traditional institutions, from Majelis Adat Aceh to syahbanda, with functions encompassing dimensions of democratic participation, conflict mediation based on restorative justice, community economic empowerment, and cultural preservation. Strengthening factors include traditional legitimacy, deeply-rooted social networks, and adaptive flexibility, while inhibiting factors encompass human resource limitations, coordination fragmentation, and cultural resistance. Recommended revitalization strategies include: (1) strengthening regulatory framework through differentiated standardization and integrated information systems; (2) integration into public policy cycles through collaborative budgeting and multi-stakeholder forums; (3) professionalization through competency certification and university partnerships; (4) domain-specific economic empowerment (panglima laot, keujreun blang, haria peukan); and (5) strengthening accountability and inclusivity of gender and youth. These findings contribute to developing hybrid governance models that integrate traditional wisdom with modern governance principles for sustainable community empowerment.